Symbiotic Relationships, Knowledge Management, and Sustainable Value at the Nexus Between Family Businesses, Cooperatives, and Rural Communities - Hadjielias, Elias; Cruz, Allan Discua; Howorth, Carole (My University, 2023)
The creation of value is a key theme in knowledge management. Researchers have identified that in rural communities, many family businesses are members of cooperatives or other consortia. Yet, there is limited understanding about how family businesses associated with a cooperative create and appropriate value. Based on an embeddedness perspective we argue that intertwined relationships between family, business, cooperative, and rural communities could create, appropriate, as well as destroy economic and social value, which can influence sustainability. We rely on a multiple case study approach of family businesses associated with a cooperative in Cyprus. Such an approach and setting are important, as they provide an opportunity to examine multiple contextual interactions. Our findings reveal the role of knowledge construction, knowledge transfer, and symbiotic relationships at the levels of family business, rural cooperative, and local community in powering processes of economic and noneconomic value creation, appropriation, and balance, which are important for community sustainability. Implications for researchers, practitioners, and policymakers, as well as future research opportunities, are presented.
Keywords: Business; Cooperatives; Economics; Encoding; family business; Knowledge management; knowledge management; rural communities; Stakeholders; Sustainable development; symbiosis; value creation